Tobacco smoking and risk of endometriosis: a systematic review and meta-analysis - Bravi, Francesca (BMJ Open, 2014)
OBJECTIVE: Since conflicting results have been published on the role of tobacco smoking on the risk of endometriosis, we provide an up-to-date summary quantification of this potential association. DESIGN: We performed a PubMed/MEDLINE search of the relevant publications up to September 2014, considering studies on humans published in English. We searched the reference list of the identified papers to find other relevant publications. Case–control as well as cohort studies have been included reporting risk estimates on the association between tobacco smoking and endometriosis. 38 of the 1758 screened papers met the inclusion criteria. The selected studies included a total of 13 129 women diagnosed with endometriosis. SETTING: Academic hospitals. MAIN OUTCOME MEASURE: Risk of endometriosis in tobacco smokers. RESULTS: We obtained the summary estimates of the relative risk (RR) using the random effect model, and assessed the heterogeneity among studies using the χ(2) test and quantified it using the I(2) statistic. As compared to never-smokers, the summary RR were 0.96 (95% CI 0.86 to 1.08) for ever smokers, 0.95 (95% CI 0.81 to 1.11) for former smokers, 0.92 (95% CI 0.82 to 1.04) for current smokers, 0.87 (95% CI 0.70 to 1.07) for moderate smokers and 0.93 (95% CI 0.69 to 1.26) for heavy smokers. CONCLUSIONS: The present meta-analysis provided no evidence for an association between tobacco smoking and the risk of endometriosis. The results were consistent considering ever, former, current, moderate and heavy smokers, and across type of endometriosis and study design.